Growth of BiFeO3 thin films by chemical solution deposition: the role of electrodes. Issue 22 (24th May 2017) - Tomczyk, Monika; Stroppa, Daniel G.; Reaney, Ian M.; Vilarinho, Paula M.
Abstract : BiFeO3 (BFO) thin films were grown by chemical solution deposition on a range of electrodes to determine their role in controlling the phase formation and microstructure of the films. Abstract : BiFeO3 (BFO) thin films were grown by chemical solution deposition on a range of electrodes to determine their role in controlling the phase formation and microstructure of the films. The crystallization on oxide electrodes followed the sequence: amorphous → Bi2 O2 (CO3 ) → perovskite, while those on Pt crystallized directly from the amorphous phase. IrO2 electrodes promoted perovskite phase formation at the lowest temperature and LaNiO3 additionally induced local epitaxial growth. All compositions exhibited fully coherent Fe-rich precipitates within the grain interior of the perovskite matrix, whereas the incoherent Bi2 Fe4 O9 second phase was also observed at the grain boundaries of BFO grown on Pt electrodes. The latter could be observed by X-ray diffraction as well as transmission electron microscopy (TEM) but coherent precipitates were only observed by TEM, principally evidenced by their Z contrast in annular dark field images. These data have pronounced consequences for the extended use of BFO films under an applied field for actuator, sensor and memory applications.